Delinquent Development Among Early-Onset Offenders: Identifying and Characterizing Trajectories Based on Frequency Across Types of Offending - Van Hazebroek, Babette C. M. (Criminal justice and behavior, 2019)
Early-onset offending is generally recognized as a risk factor for persistent criminal behavior. However, variation in long-term delinquent development among early-onset offenders remains rather underexplored and poorly understood. We, therefore, used multitrajectory modeling to identify distinct subgroups of early-onset offenders (n = 708) based on the frequency of offending across several types of offenses up to age 25. We used multinomial regression analysis to characterize subgroups on gender, ethnicity, and childhood neighborhood characteristics. Six offender subgroups could be distinguished in our data: nonrecidivists (51%), sporadic recidivists (25%), and low-rate (8%), moderate-rate (10%), high-rate adult-peaked (3%), and high-rate adolescence-peaked recidivists (3%). Males, minorities, and children from disadvantaged neighborhoods were more likely to follow re-offending trajectories characterized by increased levels of property crime, vandalism, and violent and sexual offenses. Findings are discussed in relation to criminological theory, and recommendations are made for future life-course criminological research.